PENGEMBANGAN MODUL TAJWID BERGAMBAR DENGAN PENDEKATAN MIND MAPPING UNTUK MENINGKATKAN KETERAMPILAN MEMBACA AL-QUR’AN - Imam, Imam Atim; Ruhima , Ruhima Fatharani; Tajab, Muh. Tajab; Nurjan, Syarifan Nurjan; Setiawan, Wahyudi Setiawan (TARBAWI:Journal on Islamic Education, 2024)
The development of the pictorial Tajwid module aims to explain the process of developing the pictorial Tajwid Module using a mind mapping approach and to determine the influence of developing the Pictorial Tajwid Module using a mind mapping approach on Al-Qur'an reading skills in Class XI Students at SMAN 1 Teminabuan. In this development, the research adopted a model developed referring to the Research and Development (R&D) model from Borg and Gall, this design aims to develop and validate products. A model like this has steps that must be implemented, including: (1) Information gathering, (2) Planning, (3) Product development, (4) Testing by material experts, media, language, individual trials and field trials. Data collection uses observation, questionnaires, assignments and documentation. Results of research on the development of an illustrated recitation module using a mind mapping approach. The final result of developing this module is an illustrated recitation module with a mind mapping approach in the form of an illustrated recitation book with a mind mapping approach which is used as a study guide for aspects or elements of the al-qur'an. And the results of the validation of material expert trials were 90%, media experts 94%, the results of linguist trials were 98%, individual trial results were 92%, small group trials were 90.67% and field trial results were 93.2% with results trials that have been carried out then the module is very suitable for use, In the aspect of skills assessment, after students were tested with pre-test and post-test, there was a change in learning results which reached 11.90%, an average increase from 75.05 to 86.95, so it can be interpreted that there was a development of the pictorial recitation module using the Mind mapping can be used as teaching material to improve Al-Qur'an reading skills.